Pelatihan dan Pendampingan Penggunaan Fanspage Facebook Sebagai Sarana Penjualan Online pada Remaja Nahdlatul Ulama di Simbarwaringin Kecamatan Trimurjo Kabupaten Lampung Tengah - Rakhmat Rakhmat; Habib Ismail; Mufid Arsyad; M. Diki Maulana (PT. ALHAFI BERKAH INDONESIA, 2023)
This activity aims to provide direct education and training to the youth of the Simbarwaringin Nahdlatul Ulama, Trimurjo District, Central Lampung Regency in marketing their merchandise online via the Facebook fan page. Selling online is a type of business that is run via the internet or digitally. All types of sales activities are carried out online. The internet creates a business environment where time and distance are no longer important. Sellers have access to more information that can help in making decisions and consumers have access to a wider range of products. In the current era, selling online is a method that must be used, seeing the increasingly sophisticated development of the world of social media, making it easier to market all types of products that you want to offer online. The existence of selling online is a powerful marketing and communication tool, making it a very efficient platform with an environmentally friendly way of working and a symbol of professionalism that is much needed currently. The approach method used in this community service is the PAR (Participatory Action Research) method.